Thermal behavior and polymorphism of 2, 9-didecyldinaphtho[2, 3-b:2′, 3′-f]thieno[3, 2-b]thiophene thin films. Issue 5 (4th March 2022) - Talnack, Felix; Hutsch, Sebastian; Bretschneider, Michael; Krupskaya, Yulia; Büchner, Bernd; Malfois, Marc; Hambsch, Mike; Ortmann, Frank; Mannsfeld, Stefan C. B.
Abstract : We investigate the thermal behavior and a newly found high temperature polymorph of C10-DNTT thin films experimentally and theoretically. Abstract : The ability of numerous organic molecules to adopt different crystal structures without changing their chemical structure is called polymorphism which has gained interest in recent years due to the influence it has on the solid-state properties of organic materials, e.g. charge transport in organic semiconductors. Here we present a new polymorphic crystal structure of the p-type small molecule semiconductor 2, 9-didecyldinaphtho[2, 3- b :2′, 3′- f ]thieno[3, 2- b ]thiophene (C10-DNTT). The polymorphic transition is observed during heating the films over 400 K and investigated by in situ cross-polarized optical microscopy (CPOM) and in situ grazing-incidence wide-angle X-ray scattering (GIWAXS) measurements. From these measurements, we refine the thin-film crystal structure of both the low temperature and high temperature polymorphs. We further analyze the thermal expansion of both polymorphs and perform density-functional theory (DFT) calculations to trace back the anisotropic thermal expansion to anisotropic molecular interactions.